Soil erosion studies under simulated rainfall conditions in a lateritic terrain - PRAVEENA K. K; Dr. Kurien E. K (Guide) (Tavanur 2014 DEPARTMENT OF LAND &WATER RESOURCES AND CONSERVATION ENGINEERING)
Soil erosion studies under simulated rainfall conditions in a lateritic terrain
Soil erosion studies under simulated rainfall conditions in a lateritic terrain